A Nanoscale Metal–Organic Framework to Mediate Photodynamic Therapy and Deliver CpG Oligodeoxynucleotides to Enhance Antigen Presentation and Cancer Immunotherapy. (29th November 2019) - Ni, Kaiyuan; Luo, Taokun; Lan, Guangxu; Culbert, August; Song, Yang; Wu, Tong; Jiang, Xiaomin; Lin, Wenbin
Abstract: Checkpoint blockade immunotherapy (CBI) awakes a host innate immune system and reactivates cytotoxic T cells to elicit durable response in some cancer patients. Now, a cationic nanoscale metal–organic framework, W‐TBP, is used to facilitate tumor antigen presentation by enabling immunogenic photodynamic therapy (PDT) and promoting the maturation of dendritic cells (DCs). Comprised of dinuclear W VI secondary building units and photosensitizing 5, 10, 15, 20‐tetra( p ‐benzoato)porphyrin (TBP) ligands, cationic W‐TBP mediates PDT to release tumor associated antigens and delivers immunostimulatory CpG oligodeoxynucleotides to DCs. The enhanced antigen presentation synergizes with CBI to expand and reinvigorate cytotoxic T cells, leading to superb anticancer efficacy and robust abscopal effects with >97 % tumor regression in a bilateral breast cancer model. Abstract : Das Metall‐organische Gerüst W‐TBP unterstützt die Tumorantigen‐Präsentation, indem eine immunogene photodynamische Therapie (PDT) ermöglicht und die Reifung dendritischer Zellen (DCs) gefördert wird. Die verstärkte Antigen‐Präsentation wirkt synergetisch mit der Checkpoint‐Blockade‐Immuntherapie, um cytotoxische T‐Zellen zu expandieren und wieder zu stärken, was zu einer 97‐prozentigen Tumorrückbildung in einem beidseitigen Brustkrebsmodell führte.